Fundamental psychological needs and subjective well - being: the mediating role of hope and future perspective - parisa karami dolatsha; ali taghvaeinia; fariborz Nikdel (مجله علوم روانشناختی, 2019)
Background: Fundamental psychological needs fulfillment are assumed to be major determinants of subjective well-being. Discovering the relationships of these variabeles implecation and education importance. But the important point is that mediating role of hope and future prospects in these relationships has not been examined. Aims: The purpose of this study was to investigate the relationship between basic psychological needs and subjective well-being with the mediating role of hope and future perspective of students. Method: The current research population of Khorram Abad secondary school students is 240 people who were selected by multistage cluster sampling method. In this study,  fundamental psychological needs scale for measuring  fundamental psychological needs variable, two life satisfaction questionnaires, and positive and negative affective for measuring the variables of subjective well-being, life hope scale for hoping variable and time perspective questionnaire for measuring future perspective. Results: The results of structural equation modeling showed that fundamental psychological needs is related both directly with subjective well-being and indirectly predicts subjective well-being through its impact on hope and future prospects (p<0/001). Conclusions: The results of this research emphasize the importance of recognizing the role of fundamental psychological needs, hope, and future prospects on students' subjective well-being.